Embaralhamento de pacotes e seleção de antenas como alternativa para aumentar a segurança em redes sem fio - Chiodi Junior, Marco Antônio (2016)
In this work, the use of multiple transmitting antennas with frame scrambling is proposed to increase the security of a network composed by two legitimate nodes (Alice and Bob) and a passive eavesdropper, all of them provided with multiple antennas. Considering the so-called security gap as the performance metric and assuming a quasi-static fading scenario, it was evaluated (analytically and through numerical results) the security gap based on both the outage probability and the frame error rate (using convolutional codes), showing that, in both situations, it is possible to achieve negative values of security gap with a feasible number of transmitting antennas. Moreover, it is showed that using an approximation to security gap based on outage probability, one can accurately estimate the number of antennas in Alice needed to achieve a given level of security. It is also showed that using TAS/MRC with frame scrambling, it is possible to get the same results, or almost the same, in a real case using FER when it is compared to an ideal case with outage probability.